Effect of Bacopa monniera on the Level of Cortisol Hormone in Forced Cold Water Swim Stress Induced Wistar Albino Rats - Kumar , Saravana; Thiruvengadam , Atmaram; Poovan , Punitha; Das , Priscilla; Vishnumukkala, Thirupathirao; Dhamodharan , Jagadeesh; Devi , Gayatri; Priya , Jothi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The human brain remains a mystery even after years of research into the biological processes underlying its specific actions. In recent years, researchers have identified several natural compounds that could potentially help to retard mental deterioration. Extracts of Bacopa monniera, a traditional ayurvedic medicine, have been reported to have memory-enhancing effects in animals. However, there are no studies on bp in cold stress induced neuronal changes in hippocampus have been explored. The current study examined the effects of standardized extract of Bacopa monniera, on Wistar rats. We divided the animals into 4 groups. Group I was control in which rats were kept under ideal laboratory conditions, Group II was given cold water swim stress for a period of one month after which the rats were sacrificed for histological studies to study the changes in the hippocampus caused by cold stress, Group III in which cold water swim stress given for a month followed by oral administration of normal saline as vehicle for a month, Group IV in which cold water swim stress given for a month followed by oral administration of Bacopa monniera, extracts 40mg/kg treatment for a month. Group V in which cold water swim stress given for a month followed by oral administration of Bacopa monniera, extracts 80mg/kg treatment for a month. After the treatment period blood was collected and cortisol assay was done. The data were compared with those of control rats. The results showed an increase in the cortisol level in the stressed group of rats when compared to the treatment group. These results indicate that oral administration of Bacopa monniera, extract improves the cortisol level and helps in controlling the stress in rats.